ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DI PESANTREN NURUL FALAH PANOMPUAN - Maya Sari Siregar; Rahmatika Elindra; Eva Yanti Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to analyze students’ mathematical problem solving ability on the topic of two variable linear equations system in Pesantren Nurul Falah Panompuan. The research was conducted by applying qualitative descriptive method with 4 students as the subject. . Interview and test were used in collecting the data. The data was analysis by applying data reduction, data presentation, and taking conclusion. The result of the research showed (1) students which enough category were able to understand the problems and plan problems, and (2) students which good category were able to understand the problems, plan problems, and solve the problem.